Effectiveness Combination of Torbangun Leaf and Red Guava Fruit Extract to Changes in Hemoglobin, Hematocrit, Erythrocyte and Oxygen Saturation Levels Adolescent Girls Anemia - Almas Syauqina Idzni; Mardiyono; Suryati Kumorowulan (International Journal of Allied Medical Sciences and Clinical Research, 2022)
BackgroundAnemia is a non-communicable disease that can cause various impacts such as decreased body resistance so that it is susceptible to disease, decreased fitness in thinking, decreased learning achievement or work productivity/performance. Efforts that have been made related to anemia are by giving TTD (blood boost tablets) but the incidence of anemia is still relatively high. Therapy that can be given to overcome anemia is a complementary therapy, namely torbangun leaf extract containing 113 mg/1 gram Fe and red guava fruit containing 52 mg/L vitamin C.Torbangun leaves have the advantage that they have a high Fe content, then red guava have a high vitamin C content.PurposeAnalyze the effectiveness combination of torbangun leaves extracts and red guava fruit on increasing hemoglobin, hematocrit, erythrocyte and oxygen saturation levels in adolescent girls anemia.MethodThe type of research is true experiment with a simple random sampling technique. The number of samples was 34 adolescent girls, 17 samples were in the control group, and 17 were in the intervention group. This study used a combination of extracts made into powder, namely torbangun leaves (1000 mg) and red guava fruit (500 mg) which were combined into one capsule with a dose of 1.5 grams given 3 x 1 for 14 days. The tool used to measure hemoglobin, hematocrit, erythrocytes with a hematology analyzer, and oxygen saturation using a pulse oximeter.ResultsThere was a significant increase in increasing the levels of hemoglobin, hematocrit, erythrocyte and oxygen saturation. Each treatment was assessed from the average difference in the control and intervention groups. Hemoglobin (p=0.000, 0.51±0.30 vs 1.12±0.40), hematocrit (p=0.001, 2.00±0.93 vs 3.76±1.64), erythrocyte (p=0.000, 0.16±0.10 vs 0.40±0.22), Oxygen Saturation (p= 0.000, 0.82±0.63 vs 1.94±0.65).ConclusionGiving a combination of torbangun leaf extract and red guava fruit 1.5 grams and Fe tablets are effective in increasing the levels of hemoglobin, hematocrit, erythrocyte and oxygen saturation